Knowledge and Use of Fluoride among Indiana Dental Professionals - K. M. Yoder, MSD, PhD; G. Maupome, BDS, MSc, PhD; S. Ofner, MS; N. L. Swigonski, MD, MPH (Blackwell Synergy, 2007)
This study assessed the knowledge of Indiana dentists and dental hygienists about fluoride’s predominant mode of action and their protocols for the use of fluoride for dental caries prevention.